Experimental modelling and research on vibroacoustic phenomena in machines - Pleban, D. (Archives of Acoustics, 2004)
Issues related to the development of acoustic models and determinations of energetic balances of phenomena, which occur in machines, are important factors both in the design of low-noise machines and in the prediction of machine noise. The acoustic modelling of machines may be carried out using a system of omni-directional substitute sound sources, deployed in points related to the functional elements of machines. The parameters of these sources may be determined using inversion methods. New indices - the energy transmission index and the energy radiation index, have been proposed for application in the quantitative analysis of energetic phenomena occurring in machines. Determining these indices calls for the measurement of specific vibro-acoustic parameters of machines, acoustic pressure levels and the vibration acceleration levels or vibration velocities of the surfaces of selected machine elements. The paper presents the results of experimental research in the acoustic modelling of machines with the use of inversion methods, as well as the analysis of energetic phenomena, which take place in machines.